Intervenções não farmacológicas para o controle das doenças pulmonares crônicas - Pires, Bruna Souza Vargas (2014)
Introduction: Pulmonary rehabilitation has been indicated for lung transplant candidates as a preventive and therapeutic intervention to improve patients’ functional capacity and quality of life. Objective: To evaluate the benefits of pulmonary rehabilitation on functional capacity and quality of life of patients in the waiting list or who have already been transplanted. Methodology: The potential eligible studies published until June 2014 were identified through a database search in MEDLINE, EMBASE, LILACS, Cochrane Central Register of Controlled Trials, Pedro, Web of Science, and in reference of the articles. The search was conducted using a combination of the following terms: “Pulmonary Rehabilitation” AND “Lung Transplant” OR “Lung Transplant Candidates”. Trials which the intervention consisted of pre and/or postoperative pulmonary rehabilitation programs were included. Articles that the rehabilitation included only nutritional and/or drug and/or psychosocial interventions; research that did not have pulmonary rehabilitation as the main focus and that were related to other transplanted organs; and even the ones that did not differentiate the results obtained by the transplanted organ were excluded. The main study outcomes were functional capacity and health-related quality of life, survival was shown as a secondary one. Two reviewers independently assessed the articles regarding their eligibility criteria. A third reviewer determined the inclusion of items in situations of disagreement between the other reviewers. The quality criteria of the articles were assessed by the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) instrument and in evidence-based medicine. Results: Seven articles were included in this systematic review, totaling 314 patients with a mean age of 32.5 years. There was an increase on average of 47.6 meters in the 6-minute walk test for preoperative pulmonary rehabilitation programs and 122 meters in the postoperative rehabilitation program. The maximal oxygen consumption (VO2 peak) increased, on average, 0.41 in postoperative pulmonary rehabilitation programs using cycle ergometers. The domains of physical and mental health of the SF-36 questionnaire had significant increases in the preoperative period. There was significant improvement in all domains of the SF-36 with the postoperative pulmonary rehabilitation program. The Chronic Respiratory Questionnaire (CRQ) was mentioned in just one article in the postoperative period which showed improvement in dyspnea with an increase of 0.6 points. Conclusion: Pulmonary rehabilitation is an effective intervention for both pre and post-lung transplantation. The findings suggest significant changes in functional capacity and quality of life of these patients. Methodologically, the studies should provide accurate and valid data for pre and postoperative pulmonary rehabilitation. New clinical trials on the benefits of rehabilitation should be started, keeping the concern with ethics, randomization, homogeneous groups and the logistical challenges of such tests.